Relationship between obesity indices and hypertension among middle-aged and elderly populations in Taiwan: a community-based, cross-sectional study - I-Shiang Tzeng; Yen-An Lin; Ying-Jen Chen; Yu-Chung Tsao; Wei-Chung Yeh; Wen-Cheng Li; Jau-Yuan Chen (BMJ Open)
Objective Obesity and hypertension (HTN) have become increasingly prevalent in Taiwan. People with obesity are more likely to have HTN. In this study, we evaluated several anthropometric measurements for the prediction of HTN in middle-aged and elderly populations in Taiwan.Design Cross-sectional observational study.Setting Community-based investigation in Guishan Township of northern Taiwan.Participants A total of 396 people were recruited from a northern Taiwan community for a cross-sectional study. Anthropometrics and blood pressure were measured at the annual health exam. The obesity indices included body mass index (BMI), body fat (BF) percentage and waist circumference (WC).Outcome measures Statistical analyses, including Pearson’s correlation, multiple logistic regression and the area under ROC curves (AUCs) between HTN and anthropometric measurements, were used in this study.Results Of the 396 people recruited, 200 had HTN. The age-adjusted Pearson’s coefficients of BMI, BF percentage and WC were 0.23 (p<0.001), 0.14 (p=0.01) and 0.26 (p<0.001), respectively. Multiple logistic regression of the HTN-related obesity indices showed that the ORs of BMI, BF percentage and WC were 1.15 (95% CI 1.08 to 1.23, p<0.001), 1.07 (95% CI 1.03 to 1.11, p<0.001) and 1.06 (95% CI 1.03 to 1.08, p<0.001), respectively. The AUCs of BMI, BF percentage and WC were 0.626 (95% CI 0.572 to 0.681, p<0.001), 0.556 (95% CI 0.500 to 0.613, p=0.052) and 0.640 (95% CI 0.586 to 0.694, p<0.001), respectively.Conclusions WC is a more reliable predictor of HTN than BMI or BF percentage. The effect of abdominal fat distribution on blood pressure is greater than that of total BF amount.